Relationship of Routine Inadequate Sleep Duration and Periodontitis in a Nationally Representative Sample - Wiener, R. Constance (Sleep Disord, 2016)
Purpose. Previous research has indicated the public health impact of inadequate sleep duration on health, potentially through an immune-inflammation mechanism. This mechanism also has a role in periodontitis. The purpose of this study is to determine if there is an association of routine inadequate sleep and periodontitis. Methods. Data from merged National Health and Nutrition Examination Survey years 2009-10 and 2011-12 were the data source for the study. The key outcome was periodontitis (yes, no), and the key variable of interest was usual sleep on weekday or workday nights. Chi square and logistic regression procedures were conducted. The study included 3,740 participants who were of ages 30 years and above. Results. There were 52.7% of participants who had periodontitis. There were 35.7% who usually slept less than 7 hours on weekday or workday nights. In adjusted logistic regression the odds ratio for periodontal disease for participants who slept less than 7 hours on weekday or workday night was 1.00 [95% confidence interval: 0.83, 1.21; p = .9812]. Conclusions. The relationship of periodontitis and inadequate sleep duration in a nationally representative study of participants who were of ages 30 years and above failed to reach statistical significance in adjusted logistic regression analyses.